2006
DOI: 10.1901/jaba.2006.173-05
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Control of Delay Discounting by Pathological Gamblers

Abstract: The present study demonstrated the relative impact of gambling and nongambling contexts on the degree of delay discounting by pathological gamblers. We used a delay-discounting task with 20 pathological gamblers in and out of the natural context in which they regularly gambled. For 16 of the 20 participants, it appeared that the difference of context altered the subjective value of delayed rewards, thereby producing relative changes in delay-discounting rates that were generally consistent with a hyperbolic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 30 publications
5
172
1
Order By: Relevance
“…It should be noted that other studies have reported higher values (e.g., Green et al, 1994, reported a range of 94.5%-99.9%). Group data rather than individual data were analyzed in order to calculate the discounting function; this is consistent with previous temporal discounting studies (e.g., Dixon et al, 2006) and often is necessary due to the betweensubject variability. One possibility for subject variability is that the present study employed shorter delays; consequently there was greater variability between successive time delays (i.e., there is a smaller difference between 6 months and 9 months than between 5 years and 10 years).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It should be noted that other studies have reported higher values (e.g., Green et al, 1994, reported a range of 94.5%-99.9%). Group data rather than individual data were analyzed in order to calculate the discounting function; this is consistent with previous temporal discounting studies (e.g., Dixon et al, 2006) and often is necessary due to the betweensubject variability. One possibility for subject variability is that the present study employed shorter delays; consequently there was greater variability between successive time delays (i.e., there is a smaller difference between 6 months and 9 months than between 5 years and 10 years).…”
Section: Discussionmentioning
confidence: 83%
“…Some participants always chose the LLR (7 adolescents and 3 adults); thus their data were excluded. The remaining data were further examined for departures from normality by checking that the mean of the indifference points from the three shortest delay conditions did not exceed the mean of the indifference points from the three longest delay conditions (see also Dixon, Jacobs, & Sanders, 2006). The results of 1 adolescent participant were excluded on this basis alone (i.e., the previously excluded participants also met this criterion).…”
Section: Resultsmentioning
confidence: 99%
“…Di xon, Ma rley, a nd Jacobs (2003) st ud ied delay discounting in pathological gamblers and found them to be more impulsive than matched controls. Dixon, Jacobs, and Sanders (2006) subsequently observed that delay discounting by pathological gamblers was context dependent: Gamblers discounted delayed rewards faster in a casino than when they completed the same discounting task outside a casino. These studies suggest that pathological gamblers may be impulsive in much the same way as substance abusers.…”
mentioning
confidence: 99%
“…In addition, some evidence suggests that programs that reduce drug use also can shrink k ( Figure 5C, Bickel & Odum, 1999). Other studies suggest that k changes as a function of developmental maturation (Green, Fry, & Myerson, 1994); as a function of economic inflation when the delayed outcome is money (Ostaszewski, Green, & Myerson, 1998); and in gamblers as a function of proximity to a gaming facility (Dixon, Jacobs, & Sanders, 2006).…”
Section: Quantitative Evaluation Of Modulating Effectsmentioning
confidence: 99%